Subtractive digital fabrication with actual robot and virtual material using a MARI platform. (December 2018) - Poustinchi, Ebrahim
This article presents a project-based research study using a new hybrid augmented reality platform called the Mixed Architectural Robotic Interface. Using the Mixed Architectural Robotic Interface as a mixture of different software and hardware platforms, ranging from design/modeling software, simulation engine, and an augmented reality application, the designer would be able to evaluate the possibilities/limitations of the fabrication, in real time and as part of the design. This method advances designer's understanding of the fabrication equipment as an input for the design decision-making process. This article demonstrates the potential of a virtual/actual hybridized platform as a new medium to design, simulate, and evaluate, in order to enhance the digital design and fabrication. Introducing the possibility of real-time communication between the digital design software and the fabrication platforms as well as the augmented reality simulation of the fabrication process, the Mixed Architectural Robotic Interface enables designers to test the fabrication process with the fabrication equipment in the early stages of the design process. This method makes it possible to move beyond the traditional limitations of machines pursuing "un-expected creativity, " without any additional time or cost for the process. Using the virtual material for fabrication, the Mixed Architectural Robotic Interface reduces the time and cost of having multiple iterations and encourages the hands-on experimental use of the fabrication tool (in this article robotic/computer numeric control milling) not only as a production tool but also as a design study tool.